Determinants of Customer Loyalty in Islamic Banking: The Mediating Role of Customer Satisfaction - Muhammad Daffa Dhiya’ulhaq; Rika Lidyah; Chandra Zaki Maulana (LP2M IAIN Palopo, 2026)
This study aims to examine the influence of Shariah compliance, corporate image, and relationship marketing on customer loyalty, with customer satisfaction as an intervening variable in Islamic banking. A quantitative approach with an explanatory research design was employed. Data were collected through structured questionnaires distributed to customers and analyzed using Structural Equation Modeling with the Partial Least Squares (SEM-PLS) technique. The results show that Shariah compliance, corporate image, and relationship marketing have significant positive effects on customer loyalty. In addition, these variables significantly influence customer satisfaction, which is found to have the strongest effect on customer loyalty. The mediation analysis reveals that customer satisfaction significantly mediates the relationship between Shariah compliance, corporate image, relationship marketing, and customer loyalty. This indicates that improving customer satisfaction is a key mechanism in strengthening customer loyalty. In conclusion, Islamic banks need to integrate Shariah compliance, enhance corporate image, and implement effective relationship marketing strategies to improve customer satisfaction and sustain long-term customer loyalty.